Precipitation Moisture Sources of Ethiopian River Basins and Their Role During Drought Conditions - Stojanovic, Milica; Mulualem, Getachew Mehabie; Sorí, Rogert; Vázquez, Marta; Nieto, Raquel; Gimeno, Luis (Frontiers in Earth Science, 2022)
In this study, we identified and investigated the annual climatological moisture sources for the Ethiopian river basins during 1980–2018. First, according to a cluster analysis, the 12 river basins of this country were grouped into four regions: northeast (NE), southeast (SE), southwest (SW), and west (W), which were characterised by similar annual precipitation features. Global outputs from the Lagrangian FLEXPART model were used to investigate the air mass humidity gain before reaching each region. This revealed five main oceanic moisture sources located in the Mediterranean Sea, Red Sea, Indian Ocean, Persian Gulf, and Arabian Sea, in addition to three main terrestrial moisture sources located in the African continent, Arabian Peninsula, and the regions themselves. Once the main climatological sources of moisture for each region were identified, a forward-in-time analysis of air masses over each source was performed to calculate the moisture contribution to precipitation (E – P) < 0 over the defined regions. The most important source at the annual scale for the NE, SW, and W regions is the African continent, while for the SE, it is the Indian Ocean. Indeed, terrestrial moisture sources are the major contributors (> 50%) to precipitation over the NE, SW, and W, whereas oceanic sources are the major contributors for the SE. Another analysis identified the years affected by drought conditions in the regions. The role of the sources was evaluated for those years affected by severe and extreme drought, revealing the heterogeneous and also direct influences for the regions. Finally, the impacts of annual severe and extreme drought were more prominent in areas with less vegetation change, as measured using the normalised difference vegetation index.